Platelet Function Analysis After In Vitro Treatment with Hemostasis-Affecting Components - Tigchelaar, Izaak; Monnink, Stefan HJ; Haan, Johan; Tabuchi, Noriyuki; Van Oeveren, Willem (Seminars in Thrombosis and Hemostasis, 1995)
An overall platelet function test in whole blood, which simulates conditions under arterial pressure, is useful in measuring the effect of polymer materials on blood hemostatic function. We performed biocompatibility tests with materials or plasma substitutes by interaction of blood from healthy volunteers and then subjected these blood samples to platelet function analysis (Thrombostat). We tested also the capacity of locally applied hemostatic agents for bleeding control by direct application of these agents onto the Thrombostat measuring cell. The biocompatibility tests with materials exposed to blood appeared very discriminating between compatible and noncompatible materials. The hemostatic capacity of blood exposed to noncompatible materials (assessed by binding of active thrombin) reduced markedly after one hour incubation of the material. The plasma substitutes did not affect hemostasis significantly. However, a blood dilution of 40%, as in cardiopulmonary bypass, increased the time required for closure of the measuring cell by a platelet plug exponentially. Local hemostatic agents could be selected according to their capacity to enhance platelet plug formation. In addition, ADP mixed with the hemostatic agent was most effective in improving capacity. We conclude that platelet function analysis contributes importantly to screening of materials and plasma substitutes with regard to their interaction with primary hemostasis.
Keywords: Biomaterials; plasma substitutes; hemostatic agents; Thrombostat; primary hemostasis